The collection, organization, promotion, and use of graphic novels, comics, and manga: A survey of academic libraries - Adams, Annis Lee (The Journal of academic librarianship, 2025)
As the popularity and proliferation of graphic novels, comic books, and manga has grown over the last couple of decades as well as their legitimacy as a form of literature and a subject of scholarship, academic libraries have increasingly incorporated them into their collections. However, managing these formats presents unique challenges compared to traditional materials. This study surveyed 157 academic librarians in North America to investigate how academic libraries select, acquire, organize, fund, promote, and utilize graphic literature. Findings indicate that academic libraries primarily collect graphic novels to support pleasure reading, diversify collections, and fulfill curricular needs. Libraries reported a variety of acquisition, funding, and shelving strategies. Libraries promote these materials through book displays, social media, and programming such as book clubs and themed events. Graphic novels support the curriculum across many disciplines and are sometimes used as course texts and supplemental readings. The findings highlight both innovation and inconsistency in current practices, demonstrating a wide variety of ways to select, acquire, fund, organize, shelve, promote, and utilize these works. The study provides useful information for institutions seeking to expand or reevaluate their approach to graphic literature in academic libraries. •Graphic novels are an important component of academic library collections.•Graphic novels help create a welcoming environment in academic libraries.•Graphic novels are increasingly used across the curriculum.•The management of graphic novels varies greatly among libraries.